Normal and abnormal fear and anxiety in children and adolescents - Muris, Peter (BRAT series in clinical psychology., 2007)
Written at a post-graduate level, this new volume provides a cumulative overview of the research available on the pathogenesis of fear and anxiety in youths. Its aim is to give the reader an idea of the factors that are thought to be involved in the development of abnormal fear and anxiety in children and adolescents, and to integrate this knowledge in a comprehensive model. This book also gives an update of the current scientific status on the psychological and pharmacological treatment and assessment of anxiety disorders in youths. *Reviews research literature on the cause of childhood anxiety, not only the existence and treatment *Discusses empirically supported intervention strategies *Includes questionnaires for measuring anxiety and related concepts that can be employed for research purposes *Anxiety disorders in children and adolescents is the author's primary area of research.